Crystallographic and spectroscopic characterization of a mixed actinide–lanthanide carbide cluster stabilized inside an Ih(7)-C80 fullerene cage. Issue 27 (5th March 2020) - Li, Xiaomeng; Yao, Yang-Rong; Yang, Wei; Zhuang, Jiaxin; Echegoyen, Luis; Chen, Ning
Abstract : For the first time, crystallographic and spectroscopic analyses identified that a mixed actinide–lanthanide carbide cluster Sc2 UC, with a very short UC bond, is stabilized inside an I h (7)-C80 cage. Abstract : A mixed actinide–lanthanide cluster fullerene, Sc2 UC@ I h (7)-C80, was isolated and fully characterized. For the first time, the single crystal X-ray crystallographic analysis confirms a novel actinide–lanthanide cluster Sc2 UC stabilized inside an I h (7)-C80 cage. Moreover, the UC double bond distance is 2.01 Å, the shortest UC bond confirmed by crystallography so far.